Addressing the silent threat: managing invasive Candida infections in hospitalized newborns - Zhang, Deshuang; Xie, Dongke; Yuan, Haokun; He, Na; Dong, Wenbin; Lei, Xiaoping (Frontiers in Pediatrics, 2025)
Invasive fungal infections (IFIs) remain an important problem for hospitalized newborn infants receiving intensive care, given their substantial morbidity and mortality. Candida species (Candida spp.) are the major fungal pathogens, which cause the so-called invasive Candida infections (ICIs). Of these, Candida albicans is the most commonly isolated species, followed by Candida parapsilosis. Other identified Candida spp. include Candida glabrata, Candida tropicalis, Candida krusei, etc. However, an increasing shift in the epidemiology of ICIs worldwide has been described, non-albicans Candida (NAC) spp. ICIs pose a growing threat to neonates. Herein, we examine the epidemiology of Candida spp. infections, patterns of antifungal resistance, risk factors, prevention strategies, clinical outcomes, and treatment recommendations for ICIs in hospitalized newborn infants. This review aims to provide a thorough understanding of the current evidence on ICIs to better inform targeted prevention strategies and improved treatments to reduce neonatal morbidity and mortality.